N‐acetyltransferase 10 promotes colon cancer progression by inhibiting ferroptosis through N4‐acetylation and stabilization of ferroptosis suppressor protein 1 (FSP1) mRNA. Issue 12 (8th October 2022) - Zheng, Xiao; Wang, Qi; Zhou, You; Zhang, Dachuan; Geng, Yiting; Hu, Wenwei; Wu, Changping; Shi, Yufang; Jiang, Jingting
Abstract: Background: N‐acetyltransferase 10 ( NAT10 ) is the only enzyme known to mediate the N4‐acetylcytidine (ac4C) modification of mRNA and is crucial for mRNA stability and translation efficiency. However, its role in cancer development and prognosis has not yet been explored. This study aimed to examine the possible role of NAT10 in colon cancer. Methods: The expression levels of NAT10 were evaluated by immunohistochemical analyses with a colon cancer tissue microarray, and its prognostic value in patients was further analyzed. Quantitative real‐time polymerase chain reaction (qRT‐PCR) and Western blotting were performed to analyze NAT10 expression in harvested colon cancer tissues and cell lines. Stable NAT10 ‐knockdown and NAT10 ‐overexpressing colon cancer cell lines were constructed using lentivirus. The biological functions of NAT10 in colon cancer cell lines were analyzed in vitro by Cell Counting Kit‐8 (CCK‐8), wound healing, Transwell, cell cycle, and ferroptosis assays. Xenograft models were used to analyze the effect of NAT10 on the tumorigenesis and metastasis of colon cancer cells in vivo. Dot blotting, acetylated RNA immunoprecipitation‐qPCR, and RNA stability analyses were performed to explore the mechanism by which NAT10 functions in colon cancer progression. Results: NAT10 was upregulated in colon cancer tissues and various colon cancer cell lines. This increased NAT10 expression was associated with shorter patient survival. Knockdown of NAT10 in two colon cancer cell lines (HT‐29 and LoVo) impaired the proliferation, migration, invasion, tumor formation and metastasis of these cells, whereas overexpression of NAT10 promoted these abilities. Further analysis revealed that NAT10 exerted a strong effect on the mRNA stability and expression of ferroptosis suppressor protein 1 ( FSP1 ) in HT‐29 and LoVo cells. In these cells, FSP1 mRNA was found to be modified by ac4C acetylation, and this epigenetic modification was associated with the inhibition of ferroptosis. Conclusions: Our study revealed that NAT10 plays a critical role in colon cancer development by affecting FSP1 mRNA stability and ferroptosis, suggesting that NAT10 could be a novel prognostic and therapeutic target in colon cancer.